2019
DOI: 10.48550/arxiv.1905.11844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MAGICal GRB 190114C: Implications of cutoff in the spectrum at sub-$GeV$ energies

Vikas Chand,
Partha Sarathi Pal,
Ankush Banerjee
et al.

Abstract: GRB 190114C is a famous Gamma-Ray Burst (GRB) due to its detection at sub-T eV energies by MAGIC, seen at redshift z = 0.42. This burst is one of the brightest GRB detected by Fermi . We present a detailed analysis of GRB 190114C prompt emission, using the two Fermi detectors: GBM and LAT. The LAT low energy events (LLE) data is also considered. A joint GBM-LAT analysis reveals a sub-GeV spectral cutoff. A similar high energy cutoff was reported in GRB 160509A and GRB 100724B earlier, and a handful of other so… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…and MAGIC to get a global picture and capture the diversity of these events. Studies on GRB 190114C showed multiple components in its prompt emission and a standard afterglow (Wang et al 2019;Chand et al 2019;Fraija et al 2019a). GRB 180720B showed synchrotron spectrum for prompt and a standard afterglow (Ronchi et al 2019;Fraija et al 2019b).…”
Section: Introductionmentioning
confidence: 98%
“…and MAGIC to get a global picture and capture the diversity of these events. Studies on GRB 190114C showed multiple components in its prompt emission and a standard afterglow (Wang et al 2019;Chand et al 2019;Fraija et al 2019a). GRB 180720B showed synchrotron spectrum for prompt and a standard afterglow (Ronchi et al 2019;Fraija et al 2019b).…”
Section: Introductionmentioning
confidence: 98%